THE POTENTIAL OF PROTECTING GEOGRAPHICAL INDICATIONS OF KAHAYYA COFFEE TO IMPROVE THE ECONOMY OF LOCAL COMMUNITIES - Andi Kurniawati; Qaiatul Muallima; Aso Alfian Nur (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The purpose of this study is to identify the potential of Kahayya coffee so that it can be registered through a geographic indication protection system in order to improve the economy of the local community. Data collection techniques used in this study were observation, interviews and literature study. Then analyzed using descriptive-qualitative technique. The results showed that kahayya coffee has the potential to obtain geographic indication protection because it has the reputation, quality and characteristics required in the protection of geographical indications. Protection of Geographical Indications can improve the economy of local communities and local governments, this can be seen from previous products that have registered geographical indications.